THE EFFECT OF BOARD GAMES ON STUDENTS’ COMMUNICATIVE COMPETENCE - Yanuar Dwi Prastyo; Silviyani Silviyani; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2021)
Being able to use English is the value of communication that students must have. Many students’ especially Indonesian students are still lacking in communicating using English. As teachers, we must facilitate students to be able to learn students' communicative competence. Therefore, in this study the researchers tried to use board games as learning media for students' communicative competence. Board games can create conditions that make students communicate easier to do. In this game, students are divided into groups so that students find it easier to share their opinions with their friends in small groups. The formulation of the problem in this study is there a significant effect of board games on students' communicative competence at the 10th grade of SMK Swadhipa 2 Natar? This research method uses quantitative methods. The results of this study are the average value of the control class is 0.17, while the average value of the experimental class is 0.71. It can be concluded that board games are effective for teaching students' communicative competence.